Whole-genome sequence analysis of Pseudomonas syringae pv. phaseolicola 1448A reveals divergence among pathovars in genes involved in virulence and transposition - Joardar, Vinita; Lindeberg, Magdalen; Jackson, Robert W.; J. Selengut; Dodson, Robert; Brinkac, Lauren M.; Daugherty, Sean C.; Deboy, Robert; Durkin, A. Scott; Giglio, Michelle Gwinn; Madupu, Ramana; Nelson, William C.; et al. (Journal of bacteriologyJournal of bacteriology, 2005)
Pseudomonas syringae pv. phaseolicola, a gram-negative bacterial plant pathogen, is the causal agent of halo blight of bean. In this study, we report on the genome sequence of P. syringae pv. phaseolicola isolate 1448A, which encodes 5,353 open reading frames (ORFs) on one circular chromosome (5,928,787 bp) and two plasmids (131,950 bp and 51,711 bp). Comparative analyses with a phylogenetically divergent pathovar, P. syringae pv. tomato DC3000, revealed a strong degree of conservation at the gene and genome levels. In total, 4,133 ORFs were identified as putative orthologs in these two pathovars using a reciprocal best-hit method, with 3,941 ORFs present in conserved, syntenic blocks. Although these two pathovars are highly similar at the physiological level, they have distinct host ranges; 1448A causes disease in beans, and DC3000 is pathogenic on tomato and Arabidopsis. Examination of the complement of ORFs encoding virulence, fitness, and survival factors revealed a substantial, but not complete, overlap between these two pathovars. Another distinguishing feature between the two pathovars is their distinctive sets of transposable elements. With access to a fifth complete pseudomonad genome sequence, we were able to identify 3,567 ORFs that likely comprise the core Pseudomonas genome and 365 ORFs that are P. syringae specific.
http://www.ncbi.nlm.nih.gov/pubmed/16159782?dopt=Abstract
Keywords: Bacterial Proteins; DNA, Bacterial; Genes, Bacterial; Genome, Bacterial; Molecular Sequence Data; Pseudomonas syringae; Species Specificity; virulence